Post-microtraumatic cervical osteoarthritis in a cretaceous dinosaur - R. D'Anastasio; L. Capasso (PAGEPress Publications, 2004)
The Authors describe a very rare case of osteoarthritis in a cervical vertebra of a cretaceous dinosaur (Spinosaurus maroccanus). Besides it is one of the most ancient case of osteoarthritis published up today. The fossil record was studied through macroscopic and radiographic analyses and tomography (TAC).